2022
DOI: 10.1039/d2ra05412d
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of ciprofloxacin by persulfate activated with pyrite: mechanism, acidification and tailwater reuse

Abstract: The efficient degradation of ciprofloxacin in tap and river water was investigated using the FeS2/PS system and the mechanism was studied. In addition, the tailwater after the reaction could be recycled to further reduce disposal costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…CIP is a typical antibiotic. Here, we will first discuss the degradation mechanism of CIP [27]. It has been reported that the products of CIP degradation are CO 2 , H 2 O, and intermediates, as shown in Figure 9.…”
Section: Photocatalytic Propertiesmentioning
confidence: 98%
“…CIP is a typical antibiotic. Here, we will first discuss the degradation mechanism of CIP [27]. It has been reported that the products of CIP degradation are CO 2 , H 2 O, and intermediates, as shown in Figure 9.…”
Section: Photocatalytic Propertiesmentioning
confidence: 98%